Optimization and Prevalidation of TLC-Densitometry Method for Fucoidan Analysis in Sargassum sp. Aqueous Extract - Laili Irfanah; Mochammad Yuwono; Riesta Primaharinastiti (Universitas Airlangga, 2023)
Background: Fucoidan is sulfated polysaccharide that has gastroprotector activity, and it is distributed in brown algae cell walls. Currently, there is no method for fucoidan analysis in compendia. Furthermore, analysis of Fucoidan is proven to be challenging due to the lack of chromophores and its high polarity. Objective: To develop the optimal condition of TLC-Densitometry method for fucoidan analysis in Sargassum sp. aqueous extract and to evaluate the stability of Fucoidan as a preliminary study. Methods: Chromatography was performed on Silica gel 60F254 TLC-plate as a stationary phase. The developed plate was stained with H2SO4 10% in absolute ethanol and heated in oven at 105°C for 15 minutes. Optimization is carried out by determining composition of the mobile phase, analytical wavelength, and spotting volume. Stability test of Fucoidan in standard and extract solution at 0, 4, 8, and 24 hours also 0 and 60 minutes after derivatization. Results: The optimal condition which produces a good separation of Fucoidan was achieved by using n-butanol:methanol: water (10:6:10 v/v/v) as a mobile phase, 400 nm as an analytical wavelength, and 1 µl as a spotting volume. Fucoidan was stable after storage until 24 hours. The stained spots were stable until 60 minutes after derivatization. Conclusion: Optimal condition of the TLC-Densitometry method for Fucoidan analysis was selective and can be applied to stability tests in preliminary study. Fucoidan was stable in standard solution and extracted solution until 24 hours after storage at 4°C, and the stained spots were stable until 60 minutes after derivatization.